Design aluminium sacrificial anode properties in soil corrosion - Mohd Nor Amir, Nordin (2013)
This thesis deal with the design aluminium sacrificial anode properties in soil corrosions. The main problem are sacrificial anode were used to prevent or to longer the time of corrosion of the underground pipeline metals, unfortunately the harmful chemicals such a mercury were added and it will cause the polutions to the living things and an aluminium sacrifial anode performance has lower current capacity and electrical potential. The scope is to conduct the experiment to prevent from adding harmful chemical element in Aluminum sacrificial anode.Thus, the performance is improved. There are many step before conduct the experiment. The first step is did some literature review about the corrosion and sacrificial anode behavior. Most currently sacrificial anode use magnesium, unfortunately there are some hazardous chemical mixed with it to increase their performance. Follow up with some study about an aluminium which is suitable to use on this experiment, the aluminium 6064 was decided to use in this experiment because it is suitable act as sacrificial anode. The aluminium was cutted in 5cm x 5cm for the suitable size. The aluminium was cleaned it surface by using manual grind machine.Then, the aluminium will go through some process which is heat treatment and forging process to change the grain size thus, change the performances. The sample of soil was taken at the UMP’s contruction site with pH value 5.7. The experiment was conducted on Laboratory of Corrosion in Mechanical Engineering Universiti Malaysia Pahang. Finally the conclusion about this project and the recommendations for the future plan also attached together with this thesis.